MOBILITAS DAN ALIH STATUS NELAYAN SKALA KECIL DI PROVINSI SULAWESI UTARA (Mobility and Status Exchange of Small Scale Fishermanin North Sulawesi Province) - Victoria E. N. Manoppo; Domu Simbolon; Rudy C. Tarumingkeng; Victor P. H. Nikijuluw (Buletin PSP, 2012)
North Sulawesi’s fisherman still predominated by traditional fisherman with small scale industry. This condition can trigger traditional fisherman perform a mobilization to get result of which is more to place/other area, because arrest its own region have been predominated by big scale fishermen. With condition of fisherman as elaborated above, hence require to be studied systematic and comprehensive related to Mobility and status Exchange of Small Scale Fisherman in North Sulawesi Province. Target of Research are: (1) Identifying fisherman mobility status in North Sulawesi Province., (2) Mapping factors/component having an effect on to mobility work of fisherman. Mapping resulted from impact mobility work of fisherman. Time and place of this research is conducted during 6 months, namely January 2011 up to June 2011. Research conducted in Province Sulawesi North, and intake of primary data focused at coastal countryside. Intake of sample determined by some example of region having the effort fishery catch able to deputize entire population exist in research region. Intake of fisherman household example conducted by withdrawal of random example "clustery" and is high rise (multi-stages). Type and Source Data Pursuant to target of research to reach, hence data which collected in this research consist of two type, that is: primary data and of secondary data. Analyze data which used in this research are: (1)  Descriptive Qualitative Analysis; (2) Analysis of SEM. Fisherman in North Sulawesi Province do mobility either through geographical and or work, mentioned on the basis of some consideration. As for geographical transfer of arrest area location to neighbor countryside, while transfer of work is transfer of fisherman become the non fisherman. Result of analysis of SEM mapping factors/component having an effect on to mobility work fisherman and map resulted from impact is mobility work fisherman.  Key words: mobility, small-scale fishermen, status exchange, and SEM